Terrible tyrannosaurs - Zoehfeld, Kathleen Weidner; Washburn, Lucia (New York : Scholastic, 2001)
Describes what fossils tell us about the physical characteristics and behavior of the large carnivorous Tyrannosaurus rex.
Keywords: Tyrannosaurus rex -- Juvenile literature; Tyrannosaurus rex; Dinosaurs; Fossils; Paleontology